The immigrant paradox in children and adolescents : is becoming American a developmental risk? - García Coll, Cynthia T.; Marks, Amy Kerivan (American Psychological Association, 2012)
"In this edited volume, we seek to provide a better understanding of child and adolescent development in the contexts of parent immigration to the United States during the end of the 20th century and the beginning of the 21st. The families studied in this book represent those who have experienced immigration processes in a particular time and place, or perhaps better said-- times and places. They represent part of a major demographic shift in the United States (See Chapter 1, this volume). They differ from previous waves of U.S. migrants by place of origin, language, race, and ethnicity. The earlier waves were mostly from Europe; the more recent have been from Latin America and Asia. This book is the first to devote itself to the documentation and explanation of the immigrant paradox in childhood, adolescence, and young adulthood. The book is intended for advanced undergraduates, graduate students, and colleagues in the area of immigration or ethnic studies, sociology, psychology, and education. Both authors and editors hope that our readers will increase their knowledge of immigration in general as well as of the specific and sometimes extraordinary demands this process entails and the assets and liabilities that these families have to cope with these demands. In addition, readers will learn where the immigrant paradox exists in education and behavior as well as some health outcomes among youth in immigrant families. Also elucidated here is how both settings and personal attributes contribute to the paradox and the differential outcomes observed not only by generation but by ethnic group and age. Most important, the implications for policy and practice, we hope, will come not only from our own writing but from our readers' informed interpretation and understanding of the phenomena"--Introduction. (PsycINFO Database Record (c) 2011 APA, all rights reserved).